Extracellular calcium and cAMP: second messengers as "third messengers"? - Hofer, A; Lefkimmiatis, K (2007)
Calcium and cyclic AMP are familiar second messengers that typically become elevated inside cells on activation of cell surface receptors. This article will explore emerging evidence that transport of these signaling molecules across the plasma membrane allows them to be recycled as "third messengers," extending their ability to convey information in a domain outside the cell.